Mellan frivillighet och tvång: En kvalitativ intervjustudie om socialsekreterares perspektiv på arbetet med ungdomar i riskmiljö - Wahlström,Evelina; Eckerström,Anna (2026)
Today, youth crime is a topic that recurs daily in the news and politics; the subject arouses motions both within the professional community and among private individuals. The purpose of this study was to shed light on how social workers reason and work with young people aged 15 and above who are in criminal environments. We also shed light on how motivation can contribute to young people accepting the voluntary interventions that social workers have available. The study helps draw attention to the potential challenges that social services face when motivational work is insufficient, and the concern is not sufficiently high to warrant the use of coercive interventions. Our empirical material was collected using semi-structured interviews with social workers who have a degree of Bachelor's degree in Social Work, whose work is to carry out investigations of young people who, due to their own behavior, may be in need of support or protection from social services. Using previous research and our empirical work, our study shows that motivational work is crucial in working with young people. There is a gap in the work of social workers where they experience a lack of tools to reach young people who refuse voluntary interventions, and where there is a lack of evidence for coercive interventions. We see that this may be a contributing factor to today's youth crime.
Keywords: motivation; juvenile delinquency; social worker; risk environment; deviant behavior; ungdomskriminalitet; socialsekreterare; riskmiljö; normbrytande beteende